Human MUS81: A Fence-Sitter in Cancer - Chen, Sisi; Geng, Xinwei; Syeda, Madiha Zahra; Huang, Zhengming; Zhang, Chao; Ying, Songmin (Frontiers in Cell and Developmental Biology, 2021)
MUS81 complex, exhibiting endonuclease activity on specific DNA structures, plays an influential part in DNA repair. Research has proved that MUS81 is dispensable for embryonic development and cell viability in mammals. However, an intricate picture has emerged from studies in which discrepant gene mutations completely alter the role of MUS81 in human cancers. Here, we review the recent understanding of how MUS81 functions in tumors with distinct genetic backgrounds and discuss the potential therapeutic strategies targeting MUS81 in cancer.